Neurotoxicity Associated with CD19-Targeted CAR-T Cell Therapies - Gust, Juliane; Taraseviciute, Agne; Turtle, Cameron J. (CNS drugs, 2018)
Neurotoxicity is an important and common complication of chimeric antigen receptor-T cell therapies. Acute neurologic signs and/or symptoms occur in a significant proportion of patients treated with CD19-directed chimeric antigen receptor-T cells for B-cell malignancies. Clinical manifestations include headache, confusion, delirium, language disturbance, seizures and rarely, acute cerebral edema. Neurotoxicity is associated with cytokine release syndrome, which occurs in the setting of in-vivo chimeric antigen receptor-T cell activation and proliferation. The mechanisms that lead to neurotoxicity remain unknown, but data from patients and animal models suggest there is compromise of the blood–brain barrier, associated with high levels of cytokines in the blood and cerebrospinal fluid, as well as endothelial activation. Corticosteroids, interleukin-6-targeted therapies, and supportive care are frequently used to manage patients with neurotoxicity, but high-quality evidence of their efficacy is lacking.